Differences in cost consciousness between physicians and nurses in German neonatal intensive care units. (26th July 2018) - Schmitz, Hannah; Martakis, Kyriakos; Roth, Bernd; Pfaff, Holger; Scholten, Nadine
Abstract: Aim: This study assessed the cost consciousness of nurses and physicians in German neonatal intensive care units (NICUs) and identified factors affecting cost consciousness. Methods: This study on cost consciousness was part of the German Safety4NICU study, a cross‐sectional survey conducted from 2015 to 2016. All 224 German NICUs were invited to take part in the survey, and written consent was obtained from the leading physicians and nurses. The various professions were addressed via specific questionnaires. The cost survey tool identified the participants' responsibility and their desired focus on cost consciousness. Results: Of the 1406 nurses and 496 physicians from 84 NICUs, 64.4% of the nurses and 62.5% of the physicians agreed that they shared responsibility for controlling costs. The computed score to define the overall cost consciousness level was 4.47. We identified a significantly positive association between cost consciousness, longer total clinical work experience and a decreased number of NICU intensive care beds. Increased cost consciousness was found in both men and physicians. Other hospital characteristics did not have an effect. Conclusion: Neonatology is a medical speciality where the tension between economics and the benefit of patients is extremely high. We found a moderate level of cost consciousness among NICU physicians and nurses. Abstract :